Implications of the Presence of Hyperdense Middle Cerebral Artery Sign in Determining the Subtypes of Stroke Etiology. (17th November 2021) - Sangpetch, Suchada; Wantaneeyawong, Chayasak; Soontornpun, Atiwat; Tiyapun, Nantaporn; Tanprawate, Surat; Thiankhaw, Kitti
Abstract : Background . Identifying stroke subtypes is crucial in choosing appropriate treatment, predicting outcomes, and managing recurrent stroke prevention. Objectives . To study the association of hyperdense middle cerebral artery sign (HMCAS) on noncontrast computed tomography (NCCT) brain and subtypes of stroke etiology. Methods . This is a retrospective hypothesis testing study. Patients aged 18 or over who had middle cerebral artery occlusion symptoms with HMCAS with verification on brain NCCT and received intravenous thrombolysis between January 2016 and June 2019 were enrolled. The demographic data, clinical outcomes, stroke subtypes, and characteristics of HMCAS were collected from medical records. Results . Ninety-nine out of 299 enrolled patients presented with HMCAS. The most common stroke subtype was cardioembolism (59%). Of the baseline characteristics, hypertension was more common in cases of large-artery atherosclerosis (LAA) (86.4%), and atrial fibrillation (AF) was the highest in cardioembolism (44.8%). HMCAS disappearance in cardioembolism was lowest compared to LAA and others (63% vs. 91% vs. 94.7%, respectively). The univariable analysis found that HMCAS disappearance is significantly associated with all stroke subtypes (Odds ratio, 95% confidence interval 10.58, 1.31-85.43; P = 0.027 for other and 5.88, 1.24-27.85; P = 0.026 for LAA). Multinomial logistic regression found that body weight and hypertension were associated with the LAA subtype. AF and intracranial hemorrhage (ICH) were associated with cardioembolism. Conclusion . The most likely diagnosis from the presence of HMCAS is cardioembolism, but the definite stroke etiologic subtype can not be identified. Combining the patient risk factors, including body weight, hypertension, and AF, with HMCAS and its characteristics will predict stroke subtypes more accurately.